2006
DOI: 10.1161/circulationaha.105.590398
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning Protects Against Endothelial Ischemia-Reperfusion Injury in the Human Forearm

Abstract: Background-Hypoxic cell death follows interruption of blood supply to tissues. Although successful restoration of blood flow is mandatory for salvage of ischemic tissues, reperfusion can paradoxically place tissues at risk of further injury. Brief periods of ischemia applied at the onset of reperfusion have been shown to reduce ischemia-reperfusion (IR) injury, a phenomenon called postconditioning. The aim of this study was to determine whether postconditioning protects against endothelial IR injury in humans,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
3
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 30 publications
(48 reference statements)
6
74
3
2
Order By: Relevance
“…In humans, this effect is described in the heart 5 , brain 6 , kidneys 7 , liver 8 and skeletal muscle 9 . Ischemic postconditioning, which consists on producing short periods of ischemia and reperfusion just before sustained reperfusion, also produced protective effects in rats 10 , rabbits 11 , pigs 12 and humans 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, this effect is described in the heart 5 , brain 6 , kidneys 7 , liver 8 and skeletal muscle 9 . Ischemic postconditioning, which consists on producing short periods of ischemia and reperfusion just before sustained reperfusion, also produced protective effects in rats 10 , rabbits 11 , pigs 12 and humans 13 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Experimental and clinical studies have indicated the protective effects of postconditioning in ischaemia/reperfusion injury. [17][18][19][20][21] This protection is not only associated with inhibition of inflammation and apoptosis, 22,23 but also with attenuation of oxidative stress. 3,24 The aim of the present study was to use a rat model of ischaemia/ reperfusion injury to evaluate the effects of ischaemic postconditioning on mitochondrial ROS production, in order to determine whether its inhibitory effects on oxidative stress are mediated via the mitochondrial pathway, since the golgi apparatus is also a source of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the influence of IPC on endothelial function in human models of forearm ischemia-reperfusion (IR) injury with mixed results. [16][17][18] In 11 healthy volunteers brachial FMD was measured before and after IR (20 minutes of arm ischemia followed by 20 minutes of reperfusion). 16 IR caused endothelial dysfunction (FMD 9.1 ± 1.2% pre-IR, 3.6 ± 0.7% post-IR, p < 0.001), which was prevented by three 10-second cycles (FMD 9.9 ± 1.7% pre-IR, 8.3 ± 1.4% post-IR, p = NS) or three 30-second cycles of postconditioning (FMD 10.8 ± 1.7% pre-IR, 9.5 ± 1.5% post-IR, p = NS).…”
Section: Discussionmentioning
confidence: 99%